Antibacterial and repair-promoting injectable thermosensitive hydrogel as well as preparation method and application thereof

CN117942422BActive Publication Date: 2026-11-03上海市伤骨科研究所
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311654234.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-05
Publication Date
2026-11-03
Estimated Expiration
2043-12-05

AI Technical Summary

Technical Problem

然而,现有的PEG-PAF水凝胶材料的成胶温度普遍在37℃左右,存在成胶温度较高,成胶效果较差的问题,在用于伤口促修复时的效果较差

Benefits of technology

[0028](1)本发明制备得到了一种成胶温度低、成胶效果好的可注射温敏水凝胶,其成胶温度可低至30℃,能够很好作为伤口敷料用于皮肤损伤的修复;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117942422B_ABST
    Figure CN117942422B_ABST
Patent Text Reader

Abstract

The application provides an antibacterial and wound repair-promoting injectable temperature-sensitive hydrogel and a preparation method and application thereof, and belongs to the technical field of hydrogel materials. The preparation method of the antibacterial and wound repair-promoting injectable temperature-sensitive hydrogel comprises the following steps: (1) taking methoxyl-terminated mPEG-NH2 as an initiator, and performing ring-opening polymerization on L-Ala-NCA and L-Phe-NCA as monomers to obtain a PEG-PAF polymer; (2) taking the PEG-PAF polymer solution, adding EDC / NHS to activate carboxyl groups, then adding curcumin to the solution to react, after the reaction is completed, dialysis is performed, and the product after dialysis is freeze-dried to obtain an intermediate product PEG-PAF-Cur; (3) mixing thymoquinone solution and PEG-PAF-Cur solution, and then stirring to react, after the reaction is completed, dialysis is performed, and freeze-drying is performed, so that the antibacterial and wound repair-promoting injectable temperature-sensitive hydrogel is obtained. The injectable temperature-sensitive hydrogel obtained in the application has a gelation temperature of 30 DEG C, good gelation effect, and can be well used for skin wound dressings, and in addition, the hydrogel has excellent antibacterial property and wound repair-promoting effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical hydrogel materials technology, specifically relating to an antibacterial and repair-promoting injectable thermosensitive hydrogel, its preparation method, and its application. Background Technology

[0002] Skin tissue is the largest and outermost exposed organ in the human body, playing a vital role in protecting the body from external environmental damage. However, skin tissue can be damaged after burns, accidents, and surgery, leading to impaired protective barrier function and increased susceptibility to bacterial infection. In particular, wound infections caused by drug-resistant (MDR) bacteria pose a serious problem. For example, methicillin-resistant Staphylococcus aureus (MRSA) is a prime example; it is a highly infectious and deadly bacterium that has drawn significant attention as a major MDR pathogen. Furthermore, infected wounds produce excessive reactive oxygen species (ROS), which may enhance the secretion of pro-inflammatory cytokines, leading to irreversible cell damage and prolonged inflammation. Therefore, wounds infected with MDR bacteria are often difficult to heal, severely impacting the patient's health and even threatening their life.

[0003] Given the complexity of MDR bacterial-infected wounds, ideal wound dressings should possess multiple functions, including reducing inflammation, promoting angiogenesis, inhibiting bacterial infection, and promoting tissue regeneration. To date, various biomaterials, including living cell tissues, nanofibers, hydrogels, and sponges, have been developed to promote the repair of bacterial-infected wounds. Furthermore, numerous antibacterial nanomaterials, including metal and carbon nanomaterials (gold, copper oxide, zinc oxide), have emerged as antibiotic alternatives, but their inherent limitations stem from their non-biodegradability or limited biocompatibility. Considering the complexity of wound healing in MDR bacterial infections, developing novel biocompatible biomaterials for wound healing is highly desirable.

[0004] Hydrogels have attracted considerable attention due to their advantages in maintaining a moist environment, absorbing tissue exudates, possessing soft mechanical strength similar to the extracellular matrix (ECM), and encapsulating drugs in situ. Injectable hydrogels exhibit high durability and a minimally invasive implantation process, ideally meeting the needs for good bio- and molecular integration of cell migration and proliferation, showing promise in promoting wound healing. In recent years, researchers have focused more on utilizing weak interactions (van der Waals forces, hydrogen bonds, π-π stacking, hydrophobic interactions, etc.) to mediate molecular self-assembly; constructing physically cross-linked hydrogels is another common strategy.

[0005] For example, supramolecular hydrogels are prepared by assembling triterpenoids with anti-inflammatory activity in an ethanol-water mixed solvent through three different non-covalent interactions (van der Waals forces between the compound skeletons, π-π interactions between olefinic moieties, and hydrogen bonding interactions between oxygen-containing groups), thereby enhancing wound healing efficacy. Based on ibuprofen, supramolecular hydrogels were prepared through electrostatic interactions and hydrogen bonding, exhibiting good anti-inflammatory activity and showing potential for clinical translation in the local delivery of anti-inflammatory drugs.

[0006] However, most current hydrogel-based wound healing materials are susceptible to bacterial infection, and hydrogels are particularly vulnerable to MDR bacterial infections. Therefore, the antibacterial and wound-healing effects of existing hydrogel materials still need further improvement to effectively treat wounds infected with MDR bacteria.

[0007] Photodynamic therapy (PDT) is a recognized treatment method, widely used to treat various bacteria due to its high selectivity for bacterial sites and minimal side effects. Natural photosensitizers, such as thymol (TQ), offer even better biocompatibility. TQ, as the main active ingredient in *Urechis bladderwrack*, possesses various pharmacological effects, including immunomodulation, anticancer, anti-inflammatory, anti-asthmatic, and antioxidant properties. Furthermore, TQ shows good potential in treating bacterial infections, but its hydrophobicity (1.83 g / L) limits its application. -1 Its poor bioavailability hinders its clinical deployment.

[0008] PEG-PAF hydrogel is a thermosensitive hydrogel. Using thermosensitive hydrogels to load photosensitizing drugs enables injectability and photodynamic therapy, thus enhancing the therapeutic effect of the hydrogel. However, the gelation temperature of existing PEG-PAF hydrogel materials is generally around 37℃, which results in a relatively high gelation temperature and poor gelation effect, leading to poor efficacy when used to promote wound healing.

[0009] Therefore, how to enhance the antibacterial and wound-healing properties of existing hydrogel materials, significantly reduce the gelation temperature of temperature-sensitive hydrogel materials, improve their gelation effect, and better fulfill their purpose of treating wounds and fighting infection has become an urgent technical problem to be solved. Summary of the Invention

[0010] The present invention aims to solve the aforementioned technical problems by providing an antibacterial and wound-healing injectable thermosensitive hydrogel, its preparation method, and its application. The technical objectives of this invention are twofold: firstly, to enhance the antibacterial and wound-healing properties of existing injectable hydrogels for wound treatment; and secondly, to lower the gelation temperature of existing thermosensitive hydrogel materials, thereby improving the gelation effect and better realizing their therapeutic efficacy in wound repair.

[0011] To achieve the above-mentioned technical objectives, the technical solution adopted by the present invention is as follows:

[0012] This invention first provides a method for preparing an antibacterial and repair-promoting injectable thermosensitive hydrogel, comprising the following steps:

[0013] (1) Using methoxy-terminated mPEG-NH2 as an initiator, L-Ala-NCA and L-Phe-NCA as monomers, ring-opening polymerization was carried out to prepare PEG-PAF polymer;

[0014] (2) Take the PEG-PAF polymer solution, add EDC / NHS to activate the carboxyl group, then add curcumin to react, dialyze after the reaction is completed, and freeze-dry the dialyzed product to obtain the intermediate product PEG-PAF-Cur.

[0015] (3) Mix the thymol quinone solution with the PEG-PAF-Cur solution and react them under stirring. After the reaction is completed, dialyze and freeze dry to obtain the antibacterial and repair-promoting injectable thermosensitive hydrogel.

[0016] The preparation method provided by this invention involves combining thermosensitive hydrogel PEG-PAF with TQ (thymol) and Cur (curcumin) to design and prepare a multifunctional hydrogel (TQ@PEG-PAF-Cur). Compared with PEG-PAF hydrogel (37℃), the sol-gel transition temperature of TQ@PEG-PAF-Cur is lowered to 30℃ because of the strong hydrogen bonds within the hydrogel, which is beneficial for wound isolation. Under blue light excitation, TQ@PEG-PAF-Cur generates a large number of singlet oxygen and hydroxyl radicals, exhibiting rapid and efficient antibacterial activity against MDR bacteria through photodynamic therapy. Furthermore, this hydrogel can reverse the oxidized wound microenvironment and inhibit the expression of pro-inflammatory cytokines. Therefore, TQ@PEG-PAF-Cur hydrogel can rapidly cover the wound, destroy MDR bacteria with blue light excitation, reshape the wound microenvironment, and thus accelerate wound healing.

[0017] The research results presented in this invention show that when TQ@PEG-PAF hydrogel and PEG-PAF-Cur hydrogel, which also possess thermosensitive properties, are selected, their gelation temperature is higher than 35°C. Furthermore, the antibacterial and wound-healing effects of these two hydrogels are significantly lower than those of TQ@PEG-PAF-Cur hydrogel. Therefore, the combination of TQ and Cur with the thermosensitive hydrogel PEG-PAF in this invention results in a synergistic effect between TQ and Cur, significantly enhancing the therapeutic efficacy of the composite hydrogel.

[0018] Furthermore, in step (1), the molar ratio of L-Ala-NCA monomer to L-Phe-NCA monomer is 1:1 to 3.

[0019] Furthermore, in step (1), the molar ratio of the initiator to the L-Ala-NCA monomer is 0.01 to 0.05:1.

[0020] Furthermore, in step (2), the weight ratio of PEG-PAF polymer to curcumin is 10:0.1 to 1.

[0021] Furthermore, the reaction temperature in step (2) is 25–30°C, and the reaction time is 24 h.

[0022] Furthermore, in step (3), the weight ratio of thymol to PEG-PAF-Cur is 0.01 to 1:1.

[0023] Furthermore, the carboxyl activation time in step (2) is 24 hours.

[0024] Furthermore, the mixing and stirring reaction time in step (3) is 12 hours.

[0025] The second objective of this invention is to provide an antibacterial, repair-promoting, injectable, temperature-sensitive hydrogel prepared by the above method.

[0026] A third objective of this invention is to provide the application of the antibacterial and healing-promoting injectable thermosensitive hydrogel described above in the preparation of antibacterial wound dressings.

[0027] The beneficial effects of this invention are as follows:

[0028] (1) The present invention has prepared an injectable thermosensitive hydrogel with low gelation temperature and good gelation effect. Its gelation temperature can be as low as 30°C, which can be well used as a wound dressing for the repair of skin damage.

[0029] (2) The injectable thermosensitive hydrogel prepared by the present invention has good antibacterial properties and wound healing properties, which greatly improves the effect of existing hydrogel materials in treating wound infections, especially the treatment effect against MDR bacterial infections. Attached Figure Description

[0030] Figure 1(A) Preparation routes of PEG-PAF hydrogels and functional hydrogels TQ@PEG-PAF-Cur and PEG-PAF-Cur; (B) Transmission electron microscopy (TEM) image of functional hydrogel TQ@PEG-PAF-Cur, scale bar = 20 μm; (C) Hydrodynamic particle size of functional hydrogel TQ@PEG-PAF-Cur; (D) Surface Zeta potential of different nanoparticles; (E) FTI of TQ, Cur, PEG-PAF-Cur, TQ@PEG–PAF and TQ@PEG-PAF-Cur. R spectrum; (F) XPS spectrum of TQ@PEG-PAF-Cur; (G) UV-Vis absorption spectra of TQ, Cur, PEG-PAF-Cur, TQ@PEG-PAF and TQ@PEG-PAF-Cur; (H) Fluorescence excitation and emission spectra of PEG-PAF-Cur, TQ@PEG-PAF and TQ@PEG-PAF-Cur; (I) Rheological curves of PEG-PAF and TQ@PEG-PAF-Cur; (J) Gel formation of PEG-PAF and TQ@PEG-PAF-Cur under different temperature conditions.

[0031] Figure 2 (A) FTIR spectra of L-Ala-NCA, m-PEG-NH2, L-Phe-NCA, and PEG-PAF; (B) FTIR spectra of L-Ala-NCA, m-PEG-NH2, L-Phe-NCA, and PEG-PAF. 1 H NMR spectrum.

[0032] Figure 3 XPS suture pattern in composite thermosensitive hydrogel TQ@PEG-PAF-Cur.

[0033] Figure 4 (A) Bimolecular structures and leading molecular orbitals of PEG-PAF, PEG-PAF-Cur and TQ@PEG-PAF-Cur optimized at the B3LYP / LANL2DZ theoretical level; (B) Single molecular structures and leading molecular orbitals of PEG-PAF, PEG-PAF-Cur and TQ@PEG-PAF-Cur optimized at the B3LYP / LANL2DZ theoretical level.

[0034] Figure 5The following are the UV-Vis absorption spectra of KMnO4, TQ@PEG-PAF-Cur+KMnO4, H2O2+KMnO4, PEG-PAF-Cur+KMnO4, and TQ@PEG-PAF+KMnO4: (A) UV-Vis absorption spectra of KMnO4, TQ@PEG-PAF-Cur+KMnO4, H2O2+KMnO4, PEG-PAF-Cur+KMnO4, and TQ@PEG-PAF+KMnO4; (B) ESR spectra of PEG-PAF and KMnO4 at different times (0 min, 1.0 min, 2.0 min, 3.0 min, 4.0 min, and 5.0 min); (C) ESR spectra of ·OH induced by blue light and dark light; (D) ESR spectra of ·OH induced by blue light and dark light. 1 (E) ESR spectra of O2-generated L929 cells cultured in composite hydrogel TQ@PEG-PAF-Cur at days 1, 3, and 5; (F) Live / dead analysis of HUVECs cultured in composite hydrogel at days 1, 3, and 5; (G) Proliferation of L929 cells cultured with different hydrogel material suppliers at days 1, 3, and 5; (H) Proliferation of HUVECs cultured with different hydrogel materials at days 1, 3, and 5.

[0035] Figure 6 The results of live and dead staining of L929 cells after co-incubation in each hydrogel group for (A) 1 day, (B) 3 days, and (C) 5 days, and (D) quantification of cell viability in each hydrogel group.

[0036] Figure 7 The results of live and dead staining of HUVEC cells after co-incubation in each hydrogel group for (A) 1 day, (B) 3 days, and (C) 5 days, and (D) quantification of cell viability in each hydrogel group.

[0037] Figure 8 The objectives are as follows: (A) Migration of L929 cells on hydrogel materials at different times (0h, 6h, 12h, 24h); (B) Cell migration number on various hydrogel materials; (C) Immunofluorescence images of L929 cells after 3 days, F-action stained cells, and ColI stained cells; (D) Immunofluorescence images of HUVEC cells after 3 days, F-action stained cells, and ColI stained cells; (E) and (F) ColI fluorescence intensity analysis.

[0038] Figure 9 The biofilm status of each hydrogel group, including the control group, TQ@PEG-PAF, PEG-PAF-Cur, and TQ@PEG-PAF-Cur, is shown.

[0039] Figure 10The objectives were: (A) antibacterial performance of each group of hydrogel materials against drug-resistant Escherichia coli (ESBL Ecoli); (B) quantification of the antibacterial performance of each group of hydrogel materials against drug-resistant Escherichia coli (ESBL Ecoli); (C) antibacterial activity / death status of each group of hydrogel materials against drug-resistant Escherichia coli (ESBL Ecoli); (D) antibacterial performance of each group of hydrogel materials against drug-resistant Escherichia coli (MRSA); (E) quantification of the antibacterial performance of each group of hydrogel materials against drug-resistant Escherichia coli (MRSA); (F) antibacterial activity / death status of each group of hydrogel materials against drug-resistant Escherichia coli (ESBL Ecoli); (G) generation of reactive oxygen species (ROS) in each group of hydrogel materials under light and dark conditions in bacteria; and (H) quantification of ROS fluorescence intensity.

[0040] Figure 11 Live and dead staining of each hydrogel group after antibacterial treatment with (A) ESBL Ecoli and (B) MRSA.

[0041] Figure 12 The results are as follows: (A) Schematic diagram of wound closure based on TQ@PEG-PAF-Cur composite hydrogel; (B) Changes in bacterial fluorescence intensity of MRSA fluorescent strain wounds after 1.0 min, 5.0 min, and 10.0 min of light irradiation; (C) Representative photographs of wound healing in different treatment groups at 0, 7, 14, and 21 days; (D) Number of bacteria on the wound at 7 and 14 days; (E) Changes in animal body weight in each hydrogel group; (F) Wound closure rate of each group at 7, 14, and 21 days; (G) Wound length of each group at 7, 14, and 21 days; (H) Number of bacteria on the wound at 7 and 14 days; (I) and (J) Quantitative statistics of bacteria on the wound at 7 and 14 days.

[0042] Figure 13 The results are as follows: (A) H&E staining of each group at different time points; (B) Inflammatory factors in wound healing of wounds 3 and 7 in different treatment groups.

[0043] Figure 14 Safety assessment of various hydrogel materials for heart, liver, spleen, lungs and kidneys.

[0044] Figure 15 The images are: (A) representative images of Masson staining; angiogenesis and collagen deposition in each group on days 7, 14, and 21; (B) representative images of Col I and (C) Col III immunofluorescence staining; (D) number of new hair follicles in each group; (E) and (F) quantification of the relative positive area of ​​type I and type III collagen.

[0045] Figure 16are: (A) CK14 immunofluorescence staining; (B) α-SMA immunofluorescence staining of different groups at different time points; (C) Quantification of α-SMA density in different groups; (D) Quantification of the relative positive area of CK14 in different treatment groups at different time points. Detailed Description of the Embodiments

[0046] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be specifically described below with reference to examples. It is necessary to point out that the following examples are only used to explain and illustrate the present invention, and are not intended to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above disclosure of the present invention still fall within the protection scope of the present invention.

[0047] Example 1

[0048] (1) Materials and Methods

[0049] 1. Experimental Materials and Reagents

[0050] mPEG-NH2 (Mw: ca. 5000 kDa) was purchased from Shanghai Yuanye Biotechnology Co., Ltd. N-carboxy-L-alanine anhydride and (S)-4-benzyloxyoxazolidine-2,5-dione were obtained from Aladdin Company in China. 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), cysteamine hydrochloride (CSA) and N-hydroxysuccinimide (NHS) were provided by Aladdin Inc. in China. Other reagents and chemicals are of analytical grade and purchased from Sinopharm Group in China. Curcumin and thymoquinone were purchased from Explore Platform Reagent Company. The dry DMF solution was prepared by adding anhydrous magnesium sulfate to newly purchased DMF and allowing it to stand overnight. Cell culture medium (DMEM), fetal bovine serum (FBS), phosphate buffered saline (PBS) and antibiotics were all from Gibco Life Technologies (USA). Cell Counting Kit-8 (CCK-8), Live / Dead Cell Double Staining Kit, FITC and DAPI were purchased from Solarbio Life Sciences Co., Ltd. (China). Primary antibodies and secondary antibodies were purchased from Abcam, Inc. (USA). Escherichia coli (E. coli, ATCC 25922, drug-resistant bacteria) and drug-resistant Staphylococcus aureus (S. aureus, ATCC 25923, drug-resistant bacteria) were purchased from the ATCC Center in the United States, provided by the Microbiology Laboratory of Shanghai Burn Institute. The fluorescent strain (S. aureus) was provided by Harvard University. The animals used in the experiment were provided by Shanghai SLAC Laboratory Animal Co., Ltd. (License No.: SCXK (Shanghai) 2022-0004).

[0051] 2. Experimental Equipment

[0052] The ultraviolet-visible-near-infrared spectra were obtained using a UV-3600 (Shimadu) instrument. Fourier transform infrared spectra were collected at room temperature using a Nicolet NEXUS 870 Fourier transform infrared spectrophotometer; images were taken at 1 cm⁻¹. -1 The resolution ranges from 4000 to 675 cm. -1 Scan, 64 times. 1 1H NMR was obtained on a Bruker 600MHz instrument. Fluorescence spectroscopy data were obtained using an F-7000 fluorescence spectrometer (Hitachi). Morphology and size were measured using a JEM-2100s transmission electron microscope (TEM) (100kV, HEOL). Immunofluorescence imaging of L929 and HUVEC cells was performed using a live-cell ultra-high resolution multiphoton laser confocal microscope (TCS SP8 STED 3X). In vivo fluorescence imaging of mice was performed using a chemiluminescence fluorescence imaging system (small animal optical & near-infrared II imaging system) (PerkinElmer), with an excitation wavelength of 325nm and an emission wavelength range of 400-500nm. All animal experiments were conducted in accordance with the "Animal Management Regulations" (Document No. 55 of 2001) issued by the Ministry of Health of the People's Republic of China and the "Guidelines for the Care and Use of Laboratory Animals" issued by Shanghai Jiao Tong University. Double-strength deionized water was used throughout the entire process.

[0053] 3. Preparation of PEG-PAF hydrogel

[0054] PEG-PAF (polyethylene glycol-poly(L-alanine-co-L-phenylalanine)) thermosensitive hydrogel was synthesized via ring-opening polymerization. First, methoxy-terminated PEG5000 (mPEG-NH2) was used as a macromolecular initiator, and L-Ala-NCA (L-alanine intracyclic anhydride) and L-Phe-NCA (L-phenylalanine intracyclic anhydride) were used as monomers for ring-opening polymerization.

[0055] The reaction procedure was as follows: First, 0.3217 g (2.7972 mmol) of L-Ala-NCA and 0.0667 g (0.3497 mmol) of L-Phe-NCA were added to 10 mL of DMF (N,N-dimethylformamide) solvent dried with anhydrous magnesium sulfate. The mixture was then magnetically stirred at room temperature for 30 min, followed by the addition of 0.5 g (0.1 mmol) of dried mPEG-NH2. After the reaction was complete, the product was dissolved in 20 mL of chloroform and then added dropwise to diethyl ether for precipitation and purification. This process was repeated three times to obtain the PEG-PAF polymer with a yield of 85.7%.

[0056] 4. Preparation of multifunctional thermosensitive hydrogel (TQ@PEG-PAF-Cur)

[0057] 100 mg of PEG-PAF polymer was dissolved in 50 mL of deionized water, and EDC / NHS was added for carboxyl activation for 24 h. Then, 10 mg of curcumin (Cur) was added to the above reaction mixture and reacted for 24 h. After the reaction was completed, the product was dialyzed for 3 days using a dialysis bag. The dialyzed product was then freeze-dried to obtain the intermediate product PEG-PAF-Cur.

[0058] 2 mg of thymol (TQ) was dissolved in 0.5 mL of DMSO (dimethyl sulfoxide) solution, and 10 mg of PEG-PAF-Cur was dissolved in 10 mL of deionized water. The two solutions were mixed and stirred for 12 h. After the reaction was completed, the mixture was dialyzed for 3 days and then freeze-dried to obtain the multifunctional composite thermosensitive hydrogel (TQ@PEG-PAF-Cur).

[0059] 5. Determination of the oxidizing power of hydrogels

[0060] The antioxidant capacity of TQ@PEG-PAF-Cur hydrogel was assessed by observing a color change and decreased absorbance after the addition of 0.1M KMnO4 and the comparison with H2O2, thus demonstrating that the hydrogel possesses a certain degree of antioxidant capacity.

[0061] 6. CCK-8 assay to detect cell viability

[0062] The in vitro cytotoxicity of the control group, TQ@PEG-PAF (unloaded with curcumin), PEG-PAF-Cur (unloaded with thymol), and TQ@PEG-PAF-Cur (loaded with both curcumin and thymol) hydrogels was assessed by fibroblasts (L929) and human umbilical vein endothelial cells (HUVEC) using a cell counting kit (CCK-8).

[0063] The hydrogel solution was filtered through a 0.22 μM filter and diluted with PBS to a final concentration of 20-100 mg / L. 100 μL of different hydrogel precursor solutions were added to 48-well cell culture plates at 37°C for gelation. Then, 1.0 mL of high-glucose medium (DMEM) was added to each well, and the plates were incubated for 24 h to obtain the hydrogel conditioned medium. Cell seeding was performed as described above. On day 3 post-seedling, the medium was discarded, and 100 μL of DMEM and 10 mL of CCK-8 reagent were added to each well. The mixture was gently mixed and incubated at 37°C in a 5% CO2 cell incubator for 4 h. The supernatant was discarded, and 100 μL of DMSO was added to each well. The plates were then incubated on a shaker at room temperature in the dark for 10 min. 100 μL of the reaction solution from each well was transferred to a new 96-well plate, and the absorbance at 450 nm was measured using a microplate reader.

[0064] L929 cell migration was assessed using a cell scratch assay. L929 cells were cultured to 100% confluence in 6-well cell culture plates. A linear wound was then created using a pipette tip, and cell debris was flushed off with fresh culture medium. The scratched cells were cultured for 0 h, 6 h, 12 h, and 24 h in fresh DMEM containing 10% FBS and under different hydrogel conditions. Images were captured using an inverted fluorescence microscope (OLYMPUS, Japan).

[0065] 7. Bacterial suspension co-culture method and morphological observation

[0066] A sterile 24-well plate was prepared, and 500 μL of reaction suspension was added to each well. PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur (light-exposed) were added to each well (three replicates per group). The PEG-PAF hydrogel reaction suspension was used as a control group. The plates were incubated at 37°C on a shaker (50 rpm) for 24 h. The co-cultured bacterial suspension was collected, and 100 μL of the bacterial solution was pipetted into each well of a 96-well plate. The absorbance of the bacterial solution at 600 nm was measured using a microplate reader. The co-cultured suspension was collected and plated for bacterial counting. The bacterial samples were then fixed with glutaraldehyde for 2 h, followed by sequential dehydration with ethanol-water mixtures (25%, 50%, 75%, 90%, and 100%, v / v) for 15 min each. Finally, the samples were freeze-dried and their morphology was observed using a SEM (Hitachi, SU8600, Japan).

[0067] 8. Preparation of a mouse model of full-thickness skin defect caused by infection

[0068] To further evaluate the antibacterial activity and wound healing properties of the hydrogel in vivo, a wound infection model was established in male BALB / c mice (7-8 weeks old, 18-22g, SPF grade). All animal experiments were approved by the Institutional Animal Care and Use Committee of Shanghai Jiao Tong University, and the mice were housed individually in cages at standard temperatures.

[0069] First, a skin defect with a diameter of 0.8 cm was made on each side of the back of the BALB / c mouse. A standard disc with a diameter of 0.8 cm was placed on the side of the wound. Methicillin-resistant Staphylococcus aureus suspension (10) was then applied. 8 Skin wounds in each group were infected with CFU / mL (50 μL). After 24 hours, the wounds were treated with TQ@PEG-PAF, PEG-PAF-Cur, and TQ@PEG-PAF-Cur (100 μM / mL, 100 μL) under 405 nm blue light, respectively. Wound areas were photographed and measured at different time points after treatment, and then wound tissue was excised for pathological and immunohistochemical analysis.

[0070] 9. Calculation of healing data for full-thickness skin defects in mice

[0071] (1) Using IPP6.0 software, import the wound photos of mice at various time points, select the AOI function, click "countsize" to measure the pixels of the standard disc and skin wound in the photo, and calculate the area of ​​the wound by the ratio of the two pixels.

[0072] (2) The formula for calculating the wound healing rate is:

[0073] Wound healing rate (%) = (initial wound area - residual wound area) / initial wound area × 100%.

[0074] 10. Preparation of paraffin sections of full-thickness skin defects in mice

[0075] (1) A full-thickness skin defect model of mice was prepared according to the above method. On days 3, 7, 14 and 21 after the wound was created, mice in each group (5 mice per group) were sacrificed. The normal skin tissue of the wound and surrounding area was carefully cut off 3-4 mm along the edge of the wound with ophthalmic scissors, fully flattened on sterile filter paper, and then the wound tissue was divided into two parts along the center and fixed in 4% paraformaldehyde.

[0076] (2) The next day, the wound tissue was soaked in ethanol solutions of different concentration gradients (50%, 70%, 80%, 95%, 100%, v / v) for dehydration treatment. The soaking time for each concentration of ethanol solution was 2 hours. Among them, the 100% ethanol solution needed to be soaked twice.

[0077] (3) Soak the wound tissue in an ethanol-xylene mixed solution (ethanol:xylene = 1:1, v / v) for 2 hours, and then soak it in a pure xylene solution twice, each time for 2 hours.

[0078] (4) Immerse the transparent wound tissue in paraffin powder-xylene (paraffin powder:xylene = 1:1, v / v) and bake in a 40℃ oven overnight;

[0079] (5) Adjust the oven temperature to 60°C, immerse the wound tissue in pure paraffin solution for 2 hours, then replace the paraffin solution and immerse for another 2 hours.

[0080] (6) Carefully pour liquid paraffin into the embedding frame, insert the wound tissue cut side down into the paraffin solution, and place a label on it;

[0081] (7) After the paraffin solidifies, carefully trim the wax block, then place it on the microtome, adjust the blade angle and slice it, and set the slice thickness to 5μm;

[0082] (8) Place the cut wound tissue slices in a water bath, take a detachable glass slide to retrieve the slices, and make sure that the tissue slices are spread out as much as possible on the glass slide. Then place the glass slides in a 40°C oven and bake overnight to obtain paraffin sections of mouse wound tissue.

[0083] 11. Statistical Analysis and Graphing

[0084] Experimental data are expressed as mean ± standard deviation. SPSS 13.0 software was used for statistical analysis, including one-way ANOVA and two-way ANOVA tests, on data with two or more samples. A p-value less than 0.05 was considered statistically significant. Statistical graphs were generated using Origin and GraphpadPrism 8.0 software. ("*" represents p < 0.05, "**" represents p < 0.01, and "***" represents p < 0.001).

[0085] (II) Results and Discussion

[0086] 1. Design of the multifunctional hydrogel TQ@PEG-PAF-Cur

[0087] The synthesis steps of the multifunctional composite hydrogel TQ@PEG-PAF-Cur with thermosensitive and photodynamic properties are as follows: Figure 1 As shown, it comprises a triblock polymer PEG-PAF, thymol (TQ), and curcumin (Cur). The first step involves preparing PEG-PAF-Cur by activating PEG-PAF using EDC / NHS, followed by covalently linking curcumin to the triblock polymer PEG-PAF. Next, a multifunctional thermosensitive hydrogel, TQ@PEG-PAF-Cur, is prepared by configuring a PEG-PAF-Cur hydrogel system in a specific ratio and then hydrogen-bonding thymol (TQ) into the thermosensitive hydrogel system.

[0088] While thermosensitive hydroxyl (TQ) shows promise in treating bacterial infections, its comprehensive clinical application is hindered by its hydrophobicity and low bioavailability. Therefore, a targeted drug delivery system is urgently needed to overcome the limitations of TQ. The inventors introduced curcumin into the thermosensitive material PEG-PAF. Curcumin possesses good photodynamic effects and exhibits good anti-inflammatory and antioxidant properties, preventing cell and skin tissue damage caused by high levels of reactive oxygen species (ROS). Furthermore, the introduction of curcumin enhances hydrogen bonding in the hydrogel system, leading to a decrease in the gel temperature of the thermosensitive hydrogel (e.g., ...). Figure 1 (As shown in J); On the other hand, introducing TQ into the PEG-PAF-Cur hydrogel system can improve its hydrophobicity and low bioavailability, while the introduction of TQ increases the generation of reactive oxygen species (·OH) and singlet oxygen (…). 1 The amount of O2 has a good bactericidal effect. At the same time, the temperature-sensitive properties of hydrogel can help improve the adhesion properties of the material (sol-gel transition) and isolate the external environment to avoid skin damage caused by secondary infection.

[0089] 2. Characterization of the multifunctional thermosensitive hydrogel TQ@PEG-PAF-Cur

[0090] Using field emission scanning electron microscopy (TEM) Figure 1 As shown in section B), the particle size range of the prepared thermosensitive composite hydrogel is approximately 35 nm to 65 nm, with an average particle size of about 50 nm. Further Zeta potential measurements were performed on the composite hydrogel and intermediates, and the results are as follows... Figure 1 As shown in Figure D, the introduction of Cur and TQ increases the amino functional groups, leading to a positive potential. The potentials of PEG-PAF, TQ@PEG-PAF, PEG-PAF-Cur, and TQ@PEG-PAF-Cur are 3.2 mV, 2.5 mV, 4 mV, and 3.8 mV, respectively, further indicating the successful composite of Cur and TQ.

[0091] X-ray photoelectron spectroscopy (XPS) was used to further determine that the elemental composition of the composite hydrogel TQ@PEG-PAF-Cur was C, N, O. Figure 1 (E). The emission spectrum of the composite hydrogel was measured using a fluorescence spectroscopy instrument. Figure 1 The excitation wavelengths of TQ@PEG-PAF, PEG-PAF-Cur, and TQ@PEG-PAF-Cur were 425 nm, 312 nm, and 346 nm, respectively, and the emission wavelengths were 551 nm, 548 nm, and 545 nm, respectively. With the introduction of the photosensitizer, the emission wavelengths of the composite hydrogels TQ@PEG-PAF, PEG-PAF-Cur, and TQ@PEG-PAF-Cur exhibited a certain red shift. This is mainly due to the enhanced intermolecular forces caused by hydrogen bonding between the hydrogel and the photosensitizer, resulting in a Stokes shift, further indicating the successful synthesis of the composite hydrogel.

[0092] Using Fourier transform infrared spectroscopy (FTIR) and liquid nuclear magnetic resonance hydrogen spectroscopy (FNMR) 1 Characterization by H NMR confirmed the presence of PEG-PAF, PEG-PAF-Cur, and TQ@PEG-PAF-Cur. Figure 2 As can be seen from A, for L-Ala-NCA and L-Phe-NCA at ~3450cm -1 The absorption peak near the NH vibration is at 2920 cm⁻¹. -1 and 2850cm -1 The absorption peaks are for the vibrations of -CH3 and -CH2, at 1720 cm⁻¹. -1 The characteristic absorption peak of C=O is located at 1620 cm⁻¹. -1 1450cm -1 and 1360cm -1The absorption peak of the skeletal vibration of the benzene ring is observed at 1720 cm⁻¹ after the condensation reaction to prepare PGE-PAF. -1 The vibrational absorption peak of C=O in the appendix disappears at 1250 cm⁻¹. -1 An NH2 vibrational absorption peak appears nearby.

[0093] from Figure 2 As shown in Figure B, for the raw materials L-Ala-NCA, L-Phe-NCA, and PEG-NH2, the absorption peaks around 1.2 ppm are for the -CH3 proton hydrogen vibration, around 2.5 ppm for the -CH2 proton hydrogen vibration, around 7.0 ppm for the skeletal proton hydrogen vibration, and around 9.0 ppm for the NH proton hydrogen vibration. After the reaction, the absorption peaks around 3.5 ppm are for the repeating unit proton hydrogen vibration, and around 7.2 ppm for the benzene ring proton hydrogen vibration. The broadening of these absorption peaks after the polycondensation reaction indicates that PEG-PAF was successfully prepared.

[0094] from Figure 1 As can be seen from E, after the reaction of PEG-PAF with Cur, the temperature reaches 3450 cm⁻¹. -1 The absorption peak of the stretching vibration of NH2 disappears at 1625 cm⁻¹. -1 The appearance of a skeletal vibration absorption peak at 1720 cm⁻¹ indicates the successful synthesis of PEG-PAF-Cur. When TQ is compounded with PEG-PAF-Cur, an absorption peak at 1720 cm⁻¹ is observed. -1 The appearance of a C=O vibrational absorption peak indicates that TQ has been successfully incorporated into the PEG-PAF-Cur system. From 1 The HNMR spectrum shows an absorption peak for the proton hydrogen vibration of the carbon-carbon double bond around 5.8 ppm, indicating that the synthesis of PEG-PAF and Cur was successful.

[0095] from Figure 1 The UV-Vis absorption spectrum of TQ@PEG-PAF-Cur shows that the maximum absorption peak for PEG-PAF is around 230 nm (CO), while the UV absorption peaks for PEG-PAF-Cur are at 280 nm (benzene ring), 230 nm (CO), and 420 nm, indicating that PEG-PAF-Cur has good absorption characteristics in both the visible and ultraviolet regions. When the UV absorption peaks for TQ@PEG-PAF-Cur are at 285 nm (benzene ring), 230 nm (CO), and 435 nm, it indicates that the composite hydrogel has been successfully prepared.

[0096] In biomedical applications, injectability is a key performance characteristic for the minimally invasive and localized delivery of therapeutic hydrogels. From Figure 1As can be seen from the results, the composite multifunctional hydrogel TQ@PEG-PAF-Cur is injectable and does not hinder the writing of the "SJTU" label. Meanwhile, this hydrogel exhibits good temperature sensitivity; the PEG-PAF hydrogel shows good temperature sensitivity and gelation performance at 37℃. When Cur is introduced, the gelation temperature decreases due to the strong hydrogen bonding between Cur and the PEG-PAF hydrogel. Figure 1 As can be seen from Figure J, after combining TQ with PEG-PAF-Cur, the gelation temperature decreases from 35℃ to 30℃ due to the high electronegativity of the carbonyl group on TQ forming strong hydrogen bonds with the hydrogel system. The introduction of TQ and Cur further lowers the gelation temperature. The figure also shows that at 30℃, TQ@PEG-PAF-Cur exhibits better gelation performance compared to PEG-PAF.

[0097] To further verify the stability of the hydrogel material, such as Figure 4 As shown in Figure B, we used Gaussian09 software to perform theoretical calculations, employing the B3LYP / LANL2DZ theoretical level, to perform theoretical calculations on the hydrogel groups PEG-PAF, PEG-PAF-Cur, and TQ@PEG-PAF-Cur, calculating the energy and band gap of the highest molecular occupied orbital (HOMO) and lowest molecular unoccupied orbital (LUMO) of the hydrogel materials.

[0098] Table 1. Bimolecular orbital energies of hydrogels, HOMO, LUMO, and ΔE

[0099]

[0100] Table 2. Molecular orbital energies of hydrogels, HOMO, LUMO, and ΔE.

[0101]

[0102] The calculation results show that the band gaps between the highest molecular occupied orbital (HOMO) and the lowest molecular unoccupied orbital (HOMO) of PEG-PAF, PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur are 3.5369 eV, 3.5713 eV, 3.4615 eV, and 2.5602 eV, respectively. This indicates that the introduction of Cur and TQ into the functional hydrogel PEG-PAF reduces the HOMO-LUMO band gap of the system and stabilizes the system (Table 1).

[0103] Secondly, to further verify the hydrogen bonding between molecules in the hydrogel system, we performed theoretical calculations using Gaussian 09 software, employing the B3LYP / LANL2DZ theoretical level, such as... Figure 4 As shown in Table A, the calculated band gaps for the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of the hydrogels PEG-PAF, PEG-PAF-Cur, and TQ@PEG-PAF-Cur were 3.5466 eV, 2.4348 eV, and 1.4745 eV, respectively. This indicates that the combination of Cur and TQ with the PEG-PAF hydrogel reduced the HOMO-LUMO band gap of the composite system, stabilizing the system (Table 2). Therefore, based on the designed functional hydrogel TQ@PEG-PAF-Cur, the hydrogen bonding interaction of the hydrogel composite system was determined through theoretical simulation calculations, proving that the designed functional hydrogel is theoretically feasible.

[0104] To further verify the antioxidant capacity of the temperature-sensitive hydrogel, such as Figure 5 As shown in Figure A, when a certain concentration of H₂O₂ (0.01M) is added to a KMnO₄ (0.01M) solution, the maximum absorption peak of KMnO₄ in the visible region disappears at 550 nm. After the addition of the hydrogel, the permanganate (MnO₄) in the acidic solution... - The color of MnO4 disappeared, which we believe is because... - Reduced to colorless Mn by peroxide groups 2+ Compared to TQ@PEG-PAF-Cur, the other composite hydrogel systems produced less peroxide, had weaker reducing power, and exhibited lighter solution color changes, indicating that TQ@PEG-PAF-Cur hydrogel possesses better antioxidant capacity. Figure 5 As shown in Figure B, the maximum absorption peak at 550 nm in the visible light region of the UV-Vis absorption spectrum of KMnO4 gradually disappears with increasing time, indicating that the ability to generate reactive oxygen species gradually increases over time. This further demonstrates that the hydrogel material has good antioxidant capacity and can be used in living organisms.

[0105] Electron spin resonance (ESR) using spin traps of 2,2,6,6-tetramethylpiperidine (TEMP) and 5,5-dimethyl-1-pyrrolidine N-oxide (DMPO) to directly capture short-lived singlet oxygen generated by PEG-PAF-Cur. 1 O2). After exposure to blue light irradiation, unique features can be clearly identified in the ESR spectrum. 1 O2 (1:1:1, blue line) peak mode ( Figure 5 C and Figure 5 (D). However, no significant ROS signal was found after no irradiation. Figure 4 The data from the D-scan showed that TQ@PEG-PAF@Cur produced singlet oxygen under 10 minutes of blue light irradiation.1 Compared to Cur and TQ alone, the multifunctional composite hydrogel can generate more singlet oxygen (O2) and hydroxyl radicals (·OH). 1 The presence of O2 and hydroxyl radicals (·OH) indicates that the mutual promotion between Cur and TQ can generate a large amount of ROS to kill drug-resistant bacteria.

[0106] 3. Biological behavior of L929 cells

[0107] Fibroblasts (L929 cells) participate in the entire process of tissue healing, and their migration and function affect the tissue wound healing effect. To evaluate the effects of the control group, PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur on the biological behavior of fibroblasts, the biocompatibility, proliferation, and migration of L929 cells were studied. Figure 5 China E and Figure 5 As shown in Figure F, the cell number in each group increased with increasing culture time, indicating good biocompatibility of the composite hydrogel. CCK-8 results further confirmed the proliferative activity of each cell type; after 3 days of culture, the cell numbers of PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF@Cur were significantly higher than those of the control group. Figure 5 (G and H).

[0108] To investigate the effects of PEG-PAF, PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur on the cytotoxicity, proliferation, and angiogenesis of endothelial cells, HUVEC cells were selected for the study. Figure 5 As shown in Figure F, HUVEC cells proliferated continuously in all composite hydrogels. There was no significant difference in cell proliferation between the hydrogels on day 1. On days 3 and 5, PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur showed better cell proliferation effects. Cell viability / death assays showed that cells exhibited high viability with increasing culture days, indicating good biocompatibility and no cytotoxicity of the composite hydrogels. Figure 6 and Figure 7 ).

[0109] To evaluate the effects of PEG-PAF, PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur on the biological behavior of fibroblasts, a scratch assay was performed on L929 cells. Figure 8As shown in Figure A, the cell count in each group increased with increasing culture time, indicating good biocompatibility of the composite hydrogel. After 6 h, 12 h, and 24 h of culture, the cell migration rate of the TQ@PEG-PAF-Cur composite hydrogel group was faster than that of PEG-PAF, PEG-PAF-Cur, and TQ@PEG-PAF, indicating that the TQ@PEG-PAF-Cur composite hydrogel has a better effect on promoting cell proliferation, further demonstrating that the composite hydrogel has good wound repair effect and potential.

[0110] To further evaluate the morphology and collagen secretion of L929 and HUVEC cells cultured in the composite hydrogel, immunofluorescence staining was performed. Figure 8 As shown in C and D, cell morphology was good in all groups. Cells cultured in TQ@PEG-PAF-Cur secreted more Col I compared to those cultured in TQ@PEG-PAF-Cur and PEG-PAF-Cur. Quantitative fluorescence intensity results also confirmed that cells synthesized more Col I in TQ@PEG-PAF-Cur hydrogel than in other composite hydrogels. Figure 8 (E).

[0111] Intrabacterial reactive oxygen species (ROS) detection is an indicator for assessing the amount of ROS generated by composite hydrogels. The control group, PEG-PAF-Cur, and TQ@PEG-PAF-Cur were treated under light and dark conditions, respectively, and then a ROS detection kit was added. Figure 10 As can be seen from G, TQ@PEG-PAF-Cur has a higher ability to generate reactive oxygen species compared to other composite hydrogels PEG-PAF-Cur and PEG-PAF. Figure 10 The fluorescence intensity was quantified by H. The hydrogel TQ@PEG-PAF-Cur exhibited high fluorescence intensity, indicating that the composite hydrogel can generate a large amount of reactive oxygen species, which, along with... Figure 10 The results are consistent with those in G.

[0112] The thermosensitive hydrogel composed of TQ and Cur exhibited good antibacterial properties under blue light irradiation. To evaluate the antibacterial activity of these composite hydrogels against methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Escherichia coli (ESBL Ecoli), two methods were used: bacterial counting and bacterial live / dead staining.

[0113] like Figure 10 China A and Figure 10 As shown in Figure D, compared with the control group, PEG-PAF-Cur, and TQ@PEG-PAF, the antibacterial rate of TQ@PEG-PAF-Cur after treatment with drug-resistant Staphylococcus aureus and drug-resistant Escherichia coli exceeded 99%. Figure 10 China A and Figure 10(D). Live / dead bacteria detection is an effective evaluation method based on the visual color changes of live / dead bacteria. Both live and dead bacterial cell membranes emit green fluorescence, while only the cell membranes of damaged bacteria emit red fluorescence. Fluorescence images of different composite hydrogel groups treated with drug-resistant Staphylococcus aureus (MRSA) and drug-resistant Escherichia coli (ESBL Ecoli) are shown below. Figure 11 China A and Figure 11 As shown in Figure B, compared with the control group, more fluorescence signals were observed in the PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur groups, indicating that PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur have a damaging effect on the membranes of drug-resistant Staphylococcus aureus (MRSA) and drug-resistant Escherichia coli (ESBL Ecoli).

[0114] Significant differences were found between the PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur groups and the control group, while significant differences were found between the composite hydrogel TQ@PEG-PAF-Cur group and the PEG-PAF-Cur and TQ@PEG-PAF groups. Figure 10 China A and Figure 10 (B) indicates that the composite hydrogel TQ@PEG-PAF-Cur group has good antibacterial activity. Figure 9 Biofilm live / dead staining experiments were performed on each group of hydrogels. The images show that TQ@PEG-PAF-Cur exhibited more fluorescence signals, indicating better antibacterial activity. SEM images show that, compared to the control group, PEG-PAF-Cur, and TQ@PEG-PAF, the bacterial surface of TQ@PEG-PAF-Cur showed obvious wrinkling and rupture. PEG-PAF-Cur and TQ@PEG-PAF treatments showed only minor bacterial damage to MRSA and ESBL-resistant Escherichia coli, indicating that TQ@PEG-PAF-Cur hydrogel possesses good antibacterial properties.

[0115] Hydrogels with good temperature sensitivity can significantly regulate fibroblast proliferation, collagen secretion, HUVEC growth, and angiogenesis in vitro. Therefore, to further evaluate its in vivo tissue regeneration ability, a bacterial wound infection model was established to study the effect of the composite hydrogel TQ@PEG-PAF-Cur on the healing of bacterial infected wounds. Figure 12 (A) Standardized photographic records of the healing status of the full-thickness skin wound were taken at 0, 7, 14, and 21 days postoperatively. Figure 12 (C) and ImageJ software was used to calculate the wound healing rate of each group at different time points. Figure 12As shown in Figure C, the wound healing trends were consistent across groups, but the healing outcomes differed. At each time point, the wounds treated with TQ@PEG-PAF-Cur hydrogel healed significantly faster than those in the other groups. After 7 days of treatment, the control group wounds remained moist with incomplete scab formation and a small amount of yellow exudate, while the wounds treated with PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur showed significant scab formation. This is theoretically attributed to the excellent adhesion properties of the thermosensitive hydrogel, which helps to adhere to the wound and prevent secondary infection by environmental bacteria. After 14 days of treatment, the wound area in each group was significantly reduced compared to the 7th day post-treatment. After 21 days of treatment, the wounds in the TQ@PEG-PAF-Cur group were almost completely healed; however, the control group still had larger wounds and infections. Furthermore, changes in animal weight also reveal that, notably, the TQ@PEG-PAF-Cur group showed a significant increase in weight compared to the control group, PEG-PAF-Cur group, and TQ@PEG-PAF group, indicating that the TQ@PEG-PAF-Cur group has better antibacterial and wound repair functions.

[0116] For ease of observation, Figure 12 China D and Figure 12 The dynamic healing process of each group at different time points was recorded in the data. Consistent with general observations, quantitative results at each time point also showed that the wound healing rate of the TQ@PEG-PAF-Cur group was higher than that of the control group, indicating that TQ@PEG-PAF-Cur promotes wound healing. Figure 12 (C). The wound healing rate of the TQ@PEG-PAF-Cur group was higher than that of the PEG-PAF-Cur and TQ@PEG-PAF groups, indicating that TQ@PEG-PAF-Cur has a positive effect on wound healing and also shows that TQ@PEG-PAF-Cur has a synergistic effect on promoting the healing of bacterial infected wounds.

[0117] To evaluate the effects of the control group, PEG-PAF-Cur, TQ@PEG-PAF, and TQ@PEG-PAF-Cur on wound inflammation, M1 and M2 macrophages in each group were immunofluorescently stained with CD68 / iNOS and CD68 / Arg1 on days 3 and 7 post-treatment, respectively. Figure 13 As shown in Figure B, in the early stage of inflammation (day 3), the positive level of the M1 marker iNOS in the control group was significantly higher than that in the PEG-PAF-Cur group, TQ@PEG-PAF group, and TQ@PEG-PAF-Cur group (P<0.01), indicating a more active inflammatory response. In the proliferative phase (day 7), although the expression level of iNOS decreased in all groups, the expression levels of iNOS in the TQ@PEG-PAF-Cur group and the PEG-PAF@TQ group were still lower than those in the control group and the TQ@PEG-PAF group (P<0.01). Figure 15 (E).

[0118] The M2 marker Arg1 was expressed at higher levels in the early stages of healing in the PEG-PAF@TQ and TQ@PEG-PAF-Cur groups than in the control and PEG-PAF-Cur groups (P<0.01), with the difference becoming more significant on day 7 (P<0.01). Notably, there was no significant difference between the PEG-PAF-Cur and PAF-PAF@TQ groups. These results indicate that TQ@PEG-PAF-Cur and PEG-PAF-Cur have a good inhibitory effect on inflammation in the relatively early stages of healing, which may be related to the regulation of the transformation of M1 macrophages into M2 macrophages by the presence of TQ@PEG-PAF-Cur. In addition to the role of TQ@PEG-PAF-Cur, Cur in TQ@PEG-PAF-Cur hydrogels may also be involved in inducing M2 macrophage polarization.

[0119] 4. Histological analysis

[0120] HE staining was performed on wound specimens to evaluate the histological status at 7, 14, and 21 days of healing, as well as the safety assessment of each group of hydrogel materials. Figure 13 (See Figure A). Results showed that epithelialization and granulation tissue formation occurred in the TQ@PEG-PAF-Cur and PEG-PAF-Cur groups, while wound healing was delayed in the PAF-PAF@TQ and control groups. Overall, as the wounds healed, the wound length gradually shortened and the granulation tissue thickness gradually increased in all groups, with the TQ@PEG-PAF-Cur group exhibiting the most significant trend. On day 7, only a small amount of new tissue was found in the wounds of the control, PEG-PAF-Cur, and PAF-PAF@TQ groups. The TQ@PEG-PAF-Cur group showed better granulation tissue healing, with abundant granulation tissue. Statistical data on wound length also indicated that the wound length in the TQ@PEG-PAF-Cur group was significantly shorter than that in the other groups (P<0.05), followed by the PEG-PAF-Cur group, TQ@PEG-PAF group, and control group. On days 14 and 21, the trends were similar, with the TQ@PEG-PAF-Cur group still showing the shortest wound length. Figure 12 (D). In addition, compared with other groups, the TQ@PEG-PAF-Cur group showed new granulation tissue and more complex epidermal structures, as well as skin-like appendages, on day 21.

[0121] Immunofluorescence staining of CK14 showed that, compared with other groups, the expression of CK14 in the neoepithelial tissue of the TQ@PEG-PAF-Cur and PEG-PAF-Cur groups was strongly positive at all time points, especially in the TQ@PEG-PAF-Cur group. This result confirms that the wound tissue re-epithelialization rate was significantly faster in the TQ@PEG-PAF-Cur and PEG-PAF-Cur groups compared with other groups, and the healing characteristics of the TQ@PEG-PAF-Cur group were superior to other groups. This result is consistent with HE staining. Figure 14 HE staining was performed on the heart, liver, spleen, lungs, and kidneys of each group of hydrogels to assess their biocompatibility. The results showed that each group of hydrogels exhibited good biocompatibility.

[0122] 5. Angiogenesis in the body

[0123] Enhanced angiogenesis in cultured HUVECs in vitro indicates that TQ@PEG-PAF-Cur possesses a strong angiogenic stimulating ability. Angiogenesis in wounds infected with drug-resistant bacteria was observed using α-SMA immunofluorescence staining. Figure 16 As shown in Figure B, wounds treated with TQ@PEG-PAF and those in the control group showed extremely low positive expression, with only a few blood vessels. However, the TQ@PEG-PAF-Cur group and the PEG-PAF-Cur group showed significantly increased α-SMA positive staining in the dermis, and significantly higher blood vessel density than the other groups (P<0.05). Figure 16 (C). These results suggest that the enhanced vascularization of PEG-PAF-Cur may be primarily due to the synergistic effect of Cur delivery and reactive oxygen species. Cur delivery contributes to wound closure and angiogenesis.

[0124] 6. Collagen secretion in the body

[0125] To evaluate collagen deposition and remodeling on different scaffolds at different time points, tissues were stained with Col I, Col III, and Masson staining, as well as immunofluorescence staining. Figure 15 China B and Figure 15 As shown in Figure C, on day 7, the control group had sparse collagen fibers, while the PEG-PAF-Cur and TQ@PEG-PAF groups showed higher collagen regeneration than the control group, with the TQ@PEG-PAF-Cur group having the highest collagen content. Although collagen deposition gradually increased over time, the TQ@PEG-PAF-Cur group still had more collagen fibers than the other groups, followed by PEG-PAF-Cur, TQ@PEG-PAF, and the control group. The number of hair follicles in each group was counted. Figure 15 The results showed that the TQ@PEG-PAF-Cur group had the highest number of hair follicles, proving that TQ@PEG-PAF-Cur promotes the formation of skin appendages.

[0126] Col I and Col III are the main collagen types and are associated with the efficacy and mechanisms of skin repair. Immunofluorescence staining results for Col I and Col III are shown in [link to image]. Figure 15 China B and Figure 15 The deposition of C10, Col11, and Col23 increased with time, and collagen expression in the scaffold group was higher than that in the control group (P<0.01). The expression levels of both collagens in the TQ@PEG-PAF-Cur group were higher than those in other groups, followed by the PEG-PAF-Cur and PEG-PAF-TQ groups, all of which were significantly higher than the control group. Figure 15 China E and Figure 15 These results indicate that both the TQ@PEG-PAF-Cur group and the TQ@PEG-PAF-Cur group can promote the healing of bacterial-infected wounds by promoting the deposition and remodeling of both types of collagen.

[0127] The above results demonstrate that the thermosensitive hydrogel composite with Cur and TQ has good therapeutic effects. Therefore, it has high potential in promoting the healing of bacterial infection wounds and is an ideal precision treatment strategy for tissue regeneration.

Claims

1. A method for preparing an antibacterial and repair-promoting injectable thermosensitive hydrogel material, characterized in that, Includes the following steps: (1) Using methoxy-terminated mPEG-NH2 as an initiator, L-Ala-NCA and L-Phe-NCA as monomers, ring-opening polymerization was carried out to prepare PEG-PAF polymer; (2) Take the PEG-PAF polymer solution, add EDC / NHS to activate the carboxyl group, then add curcumin to react, dialyze after the reaction is completed, freeze dry the dialyzed product to obtain the intermediate product PEG-PAF-Cur; (3) Mix the thymol quinone solution with the PEG-PAF-Cur solution and react them under stirring. After the reaction is completed, dialyze and freeze dry to obtain the antibacterial and repair-promoting injectable thermosensitive hydrogel material.

2. The preparation method according to claim 1, characterized in that, In step (1), the molar ratio of L-Ala-NCA monomer to L-Phe-NCA monomer is 1:1~3.

3. The preparation method according to claim 1, characterized in that, In step (1), the molar ratio of the initiator to the L-Ala-NCA monomer is 0.01~0.05:

1.

4. The preparation method according to claim 1, characterized in that, In step (2), the weight ratio of PEG-PAF polymer to curcumin is 10:0.1~1.

5. The preparation method according to claim 1, characterized in that, The reaction temperature in step (2) is 25~30℃ and the reaction time is 24h.

6. The preparation method according to claim 1, characterized in that, In step (3), the weight ratio of thymol to PEG-PAF-Cur is 0.01 to 1:

1.

7. The preparation method according to claim 1, characterized in that, The carboxyl activation time in step (2) is 24 hours.

8. The preparation method according to claim 1, characterized in that, The mixing and stirring reaction time in step (3) is 12 hours.

9. An antibacterial, repair-promoting injectable thermosensitive hydrogel material prepared by the method according to any one of claims 1-8.

10. A hydrogel prepared from the antibacterial and repair-promoting injectable thermosensitive hydrogel material according to claim 9.

11. The use of the hydrogel material of claim 9 or the hydrogel of claim 10 in the preparation of antibacterial wound dressings.